Vietnam’s energy-related carbon emissions projections for the shared socioeconomic pathways towards net zero emission: a system dynamic analysis - Hoang Ha, Anh; Da Hanh, Tran Minh (International Journal of Sustainable Energy Planning and Management, 2024)
Vietnam, a rapidly growing economy with high energy demand, aims for net-zero emissions by 2050. This study employs a system dynamic model to analyze the complex dynamics of energy-related carbon emissions. Historical data from 1990 to 2020 and predictions up to 2050 under five shared socioeconomic pathway (SSP) scenarios were used. Sensitivity analysis identifies GDP.PPP growth rate, energy intensity, and energy structure as key drivers of energy consumption and carbon emissions. Predictions show that energy consumption and emissions peak in SSP5, followed by SSP1, SSP2, SSP4, and SSP3. By 2050, Vietnam's energy consumption and carbon emissions are expected to peak at 16,536,323 TJ and 1001 Mt CO2, respectively. While all scenarios meet the 2030 emission targets, they fail to meet the 2050 targets, with SSP5 requiring the most significant emission reductions. Without robust policy interventions, Vietnam may struggle to achieve its net-zero emission goal, emphasizing the need to promote energy-efficient sectors and transition to renewable energy sources.